KECERDASAN EMOSI DAN KONFORMITAS TEMAN SEBAYA DENGAN PERILAKU BULLYING - Annisa Fitriani; Septiyanah Septiyanah (Psyche: Jurnal Psikologi, 2020)
Bullying behavior is a desire or negative action to injure both physically, verbally or psychologically committed by a person or group of people to others repeatedly, in this case, there is an imbalance of power between the perpetrators and victims whose effects are very detrimental to the perpetrators and victims. This study aims to determine the relationship between emotional intelligence and peer conformity with bullying behavior in adolescents. The data collection method uses three psychological scales which include: bullying behavior scale, emotional intelligence scale, and peer conformity scale. The research is in SMP Nusantara Bandar Lampung. The population in this study was 343 students. The number of research samples of 60 students was taken using a purposive sampling technique. The data analysis technique used was a multiple regression analysis of the predictors. Based on the analysis of the results of the research results Rx1.2-y = 0.542 and p = 0,000 (p <0.01) which means there is a significant relationship between emotional intelligence and peer conformity with bullying behavior in students. These results made an effective contribution of 29.4%.Keywords: Emotional Intelligence; Peer Conformity; Bullying Behavior